2005
DOI: 10.1128/jvi.79.4.2079-2086.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Beta Interferon Induction by Severe Acute Respiratory Syndrome Coronavirus Suggests a Two-Step Model for Activation of Interferon Regulatory Factor 3

Abstract: Severe acute respiratory syndrome (SARS) is caused by a novel coronavirus termed SARS-CoV. We and others have previously shown that the replication of SARS-CoV can be suppressed by exogenously added interferon (IFN), a cytokine which is normally synthesized by cells as a reaction to virus infection. Here, we demonstrate that SARS-CoV escapes IFN-mediated growth inhibition by preventing the induction of IFN-␤. In SARS-CoV-infected cells, no endogenous IFN-␤ transcripts and no IFN-␤ promoter activity were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
275
5
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 274 publications
(305 citation statements)
references
References 74 publications
(94 reference statements)
22
275
5
3
Order By: Relevance
“…We suspect that nsp1 promoted degradation of IFN-␤ mRNA in SeV-infected cells. Others (18) demonstrated that IRF-3 dimerization is blocked in SCoV-infected 293 cells, so we think that at least two different mechanisms inhibit IFN-␤ mRNA accumulation in SCoV-infected cells: One suppresses a signaling pathway that activates IRF-3 and the other is the nsp1-mediated promotion of IFN-␤ mRNA degradation. Dual means of inhibiting IFN-␤ mRNA accumulation would seem to be crucial for SCoV to establish infection in the host, because SCoV is known to be susceptible to IFN treatment (19,20).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…We suspect that nsp1 promoted degradation of IFN-␤ mRNA in SeV-infected cells. Others (18) demonstrated that IRF-3 dimerization is blocked in SCoV-infected 293 cells, so we think that at least two different mechanisms inhibit IFN-␤ mRNA accumulation in SCoV-infected cells: One suppresses a signaling pathway that activates IRF-3 and the other is the nsp1-mediated promotion of IFN-␤ mRNA degradation. Dual means of inhibiting IFN-␤ mRNA accumulation would seem to be crucial for SCoV to establish infection in the host, because SCoV is known to be susceptible to IFN treatment (19,20).…”
Section: Discussionmentioning
confidence: 87%
“…IRF-3 phosphorylation, dimerization, nuclear translocation, and association with CBP͞p300, all of which are essential for IFN-␤ mRNA transcription, do not occur in SCoV-infected 293 cells (18). We next examined the effect of nsp1 expression on the SeV-induced IRF-3 homodimerization and found that neither nsp1 nor NSs expression blocked dimerization (Fig.…”
Section: Nsp1 Protein Suppresses Ifn-␤ Mrna Accumulation Without Inhimentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, many different viruses evade an immune response by interfering with transcriptional activation of IFN-α/β genes [59]. Notably, in order to escape activation of the IFN system, the SARS-CoV appears to block a step after the early nuclear transport of IRF-3, the transcription factor essential for IFN-β and IFN-α4 promoter activity [60].…”
Section: Discussionmentioning
confidence: 99%